Securitization, Islamic chaplaincy, and the issue of (de)radicalization of Muslim detainees in Dutch prisons - Vellenga, Sipco J. (Social compass, 2019)
What position does organized Muslim chaplaincy in Dutch prisons take with respect to the prevention of radicalization and to the de-radicalization of detainees with a Muslim background? After describing the process of securitization of Salafism in the Netherlands, discussing the use of context-related concepts as radicalization, extremism and terrorism, and sketching the context and the making of Muslim chaplaincy, the article provides a brief overview of recent research on the relation between detention and (de)radicalization. Then, the stance of Islamic prison chaplaincy towards (de)radicalization of Muslim prisoners is described and analyzed in terms of goals, policy and practice. An expansive oligopolistic system of chaplaincy, representing various organized religions, seems to facilitate a relatively a-political type of Islamic chaplaincy, which often acts as a countervailing force to the dominant trend of securitization.